2018
DOI: 10.1142/s2251171718400056
|View full text |Cite
|
Sign up to set email alerts
|

FORCAST: A Mid-Infrared Camera for SOFIA

Abstract: We describe the Faint Object infraRed CAmera for the SOFIA Telescope (FORCAST) which is presently operating as a facility instrument on the Stratospheric Observatory For Infrared Astronomy (SOFIA). FORCAST provides imaging and moderate resolution spectroscopy capability over the 5–40[Formula: see text][Formula: see text]m wavelength range. In imaging mode, FORCAST has a 3.4[Formula: see text] field-of-view with 0.768[Formula: see text] pixels. Using grisms, FORCAST provides long-slit low-resolution ([Formula: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…SOFIA is a 2.5 m telescope flown on a Boeing 747-SP aircraft used for infrared and submillimetre astronomy 29 . The FORCAST instrument combines a spectrograph and a mid-infrared camera using a 256 × 256 Si Blocked-Impurity-Band infrared focal plane array 30 . For lunar observations, we used the FORCAST G063 filter with the long-slit (2.4 × 191″) low-resolution mode to provide a spectral coverage of 5 to 8 µm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SOFIA is a 2.5 m telescope flown on a Boeing 747-SP aircraft used for infrared and submillimetre astronomy 29 . The FORCAST instrument combines a spectrograph and a mid-infrared camera using a 256 × 256 Si Blocked-Impurity-Band infrared focal plane array 30 . For lunar observations, we used the FORCAST G063 filter with the long-slit (2.4 × 191″) low-resolution mode to provide a spectral coverage of 5 to 8 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The data are in the form of spectral images that are 248 × 248 pixels, where the x axis is wavelengths covering 5 to 8 µm and the y axis is the spatial position on the Moon along the spectrograph slit. Data were processed using the standard SOFIA corrections 30 . The processing steps are shown in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The wavelength coverage and capabilities of MISC-T and MISC WFI partly overlap with those of JWST/mid-infrared instrument (MIRI), 18 SOFIA instruments: Faint Object infrared Camera for the SOFIA Telescope, 19 Echeleon-Cross-Echelle Spectrograph, 20 Space Infrared Telescope for Cosmology and Astrophysics (SPICA, a mission under study for ESA/JAXA) instrument studies: SPICA Mid-infrared Instrument (SMI, current), 21 Mid-infrared Camera and Spectrometer, 22 SPICA Coronagraph Instrument (SCI), 23 Tokyo Atacama Observatory (TAO) Multi-field Imager for gazing at the UnKnown Universe (MIMIZUKU), 24,25 Spitzer/IRS, 26 and Thirty Meter Telescope Mid-Infrared Camera High-disperser & IFU (MICHI), 27 and NEOSM. 9 Particularly, the long-wavelength HgCdTe detectors, which are employed in MISC-T-S and T-M, have been developed for the NEOSM (See details for Ref.…”
Section: Misc Heritage and Maturitymentioning
confidence: 99%
“…Observations of the galactic center presented by Iserlohe et al 13 showed how the ability of FIFI-LS to quickly map large areas in multiple fine diagnostic lines was used to characterize photodissociation regions (PDR). Line emission maps of four lines: [CII], [OI] 63 and 145 μm, and CO J ¼ 14 to 13 as well as the FIR flux derived using FIFI-LS, FORCAST, 14 and PACS continuum data were used to infer the density and FUV-field using PDR models. 15 The analysis by Iserlohe et al shows that the [OI] line fluxes at ∼63 μm have to be affected by self-absorption, whereas there is significant contribution to the [CII] line flux not originating from the probed PDR.…”
Section: Science With Fifi-lsmentioning
confidence: 99%